Percepções na docência em Educação Física: a formação do ser professor a partir de Merlau-Ponty - Telles, Cassiano (2019)
This research aims to understand the perception that teachers have of their formation in Physical Education about the exercise of teaching. For this, we will use as a basis of theoretical support the foundations of the phenomenological perspective of Merleau-Ponty, where the author proposes to discuss the creative possibility of meaning for existence in the world. The philosopher presents the perceived field as a set of organized phenomena, which, due to their natural capacities, produce understandings understood by all subjects, regardless of their language or culture. The research paths were based on a qualitative study, with a phenomenological focus, consisting of the speech of the subjects as their methodological option. This is based on field research in exploratory-descriptive mode, which has the sense of investigating the relationship between methodology, theory and practice, generating the educational phenomenon. This study is characterized as a case study, as our focus is on the Physical Education teachers of a particular city in the northwest of Rio Grande do Sul, more specifically eight (8) teachers. For this study, we used semi-structured interview and field observation, because we believe this is the best way to acquire information to reach the proposed objectives. We understand that being a teacher when externalizing his perception shows us his look is: about himself, about his peers and about the academic world, so we can describe the different perspectives at different stages of the school career. The importance of this theme is made to value the personal and professional development of teachers through understanding with regard to their existence, giving them a notion of the reality of how they are acting and the very formation acquired as a subject that expresses human needs, Thus, when we observe the teacher, we can realize that his environment and his relationships go beyond the analysis of his practice and his speech, and thus, we can evidence him as an incarnate being in the world.